Do we Know how they Learn? - Hussain, Habiba (Journal of Engineering Education Transformations, 2005)
Every individual has his/her own style of learning, whatever be the age of the learner: Many studies have been conducted on learning style and related aspects. This snap study was undertaken to study the learning style of students pursuing higher education. Also, efforts were made to observe the learning outcomes focused by the teachers and the methods used by them for teaching. It is very astonishing as also alarming to find that ill spite of having known the consequences, teachers are bound to follow the age old method of lecturing in the classrooms. In this paper, a view of the learning preferences of such learners has been depicted vis-a-vis the learning outcomes prioritized by teachers. Some recommendations have also been suggested so as to cater to the divergent learning needs of students even while following the lecture method for instruction.